Polyketones as Host Materials for Solid Polymer Electrolytes. Issue 7 (13th March 2020) - Eriksson, Therese; Mace, Amber; Manabe, Yumehiro; Yoshizawa-Fujita, Masahiro; Inokuma, Yasuhide; Brandell, Daniel; Mindemark, Jonas
Abstract : While solid polymer electrolytes (SPEs) have great potential for use in future lithium-based batteries, they do, however, not display conductivity at a sufficient level as compared to liquid electrolytes. To reach the needed requirements of lithium batteries it is therefore necessary to explore new materials classes to serve as novel polymer hosts. In this work, SPEs based on the polyketone poly(3, 3-dimethylpentane-2, 4-dione) were investigated. Polyketones are structurally similar to several polycarbonate and polyester SPE hosts investigated before but have, due to the lack of additional oxygen atoms in the coordinating motif, even more electron-withdrawing carbonyl groups and could therefore display better properties for coordination to the salt cation. In electrolyte compositions comprising 25−40 wt% LiTFSI salt, it was observed that this polyketone indeed conducts lithium ions with a high cation transference number, but that the ionic conductivity is limited by the semi-crystallinity of the polymer matrix. The crystallinity decreases with increasing salt content, and a fully amorphous SPE can be produced at 40 wt% salt, accompanied by an ionic conductivity of 3 × 10 −7 S cm −1 at 32 °C. This opens up for further exploration of polyketone systems for SPE-based batteries.